HOW TO PREVENT SOCIAL CONFLICTS FROM BECOMING ARMED CONFLICTS (Journal of the Spanish Institute for Strategic Studies, 2018)
There are voices within academia that deem it impossible to predict armed conflict on the basis of the polemological analysis of its causes. Yet, in any armed conflict, in addition to its causes, we see actors and circumstances that surround such conflict and that condition its evolution. This leads us to believe that the answer to the question about whether it is possible to prevent a social conflict from becoming an armed conflict could lie in the study of these actors and circumstances. This article will reveal an avenue for research that could provide a response to the proposed hypothesis.